The New Resource Management in U.S. Workplaces: Is it Really New and is it Only Nonunion? - Ichniowski, Casey; Delaney, John; Lewin, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper uses new data on business units to document the type and extent of human resource management policies and practices currently in place in unionized and nonunion businesses in the United States.